A binary formulation of SAIDI for the predictive reliability assessment of radial distribution systems with tie lines - Tio, Adonis Emmanuel DC
Distribution system engineers can optimize distribution system reliability through the optimal placement of reclosers, fuse-blow fuses, fuse-save fuses, switches, and tie lines. Currently, there is no objective function formulation that is explicitly expressed as a function of the locations of these devices. This situation presents a barrier to the application of mathematical methods for reliability optimization. This thesis presents such a formulation: a binary System Average Interruption Duration Index (SAIDI) formulation explicitly expresses as a function of the placement of reclosers, fuse-blow fuses, fuse-save fuses, switches, and tie lines in a radially operated distribution system. This formulation can be used (1) for predictive reliability assessment as an alternative assessment methodology and (2) for reliability optimization as an objective function that is compatible with deterministic, heuristic, and stochastic optimization approaches. This formulation can be easily modified to model the Average System Interruption Duration Index (ASIDI) and the Expected Energy Not Supplied (EENS). We were able to validate this formulation using published results and an established predictive reliability assessment method. Furthermore, we demonstrated that this formulation can be used in finding the global optimal SAIDI of distribution systems.